The Effectiveness of the Outlining Technique in Overcoming Writing Difficulties in Descriptive Text Among Eighth-Grade Students of SMP Negeri 31 Medan - Medianti Simanjuntak; Meikardo Samuel Prayuda; Fiber Yun Almanda Ginting (Jurnal Pendidikan Indonesia, 2026)
This study aims to investigate the effectiveness of the outlining technique in improving students’ writing skill in descriptive texts among Grade VIII students of SMP Negeri 31 Medan in the 2025–2026 academic year. This study is motivated by students’ low writing skill in descriptive texts, particularly in developing ideas, organizing text structure coherently, and using appropriate vocabulary and grammar. This research employed a quantitative approach with a quasi-experimental design using a pre-test and post-test control group design. The sample consisted of 60 Grade VIII students, divided into two groups: the experimental class (VIII-7) and the control class (VIII-8), each consisting of 30 students selected through purposive sampling. The experimental group was taught using the outlining technique, while the control group was taught using conventional teaching methods. The data were collected through pre-test and post-test assessments and analyzed using normality test, homogeneity test, independent samples t-test, and paired sample t-test. The results of the study indicate that there is a significant difference between the experimental and control groups based on the independent samples t-test result, with a t-value of 6.063 and a significance level of 0.000 < 0.05, leading to the rejection of H₀ and acceptance of Hₐ. Furthermore, the paired sample t-test results show that both groups experienced a significant improvement; however, the experimental group achieved a higher increase compared to the control group. The mean score of the experimental group increased from 69.33 to 88.33, while the control group increased from 62.33 to 77.17. Therefore, it can be concluded that the outlining technique is effective in improving students’ writing skill in descriptive texts.